Penerapan Strategi Pemasaran Digital Melalui Media Sosial Di Surya Jaya Sedadi - Sri Martono; Indah rahayu (LPPM Universitas An Nuur, 2023)
Background: The increasingly rapid advances in technology have brought various changes to every aspect of life, starting from the cultural, political, social and economic fields. In recent years, the development of the internet has had an impact, especially in the business sector. Even though there are negative impacts, the presence of the internet also creates great opportunities in the business world. Likewise with Surya Jaya Sedadi, with the presence of the internet, it has become easier to manage its business, even with this technology, it has been able to increase its sales value. Purpose: The aim of this research is to identify how to implement digital marketing strategies through social media in surya jaya sedadi. Methods: The research method used is content analysis method and literature survey to define concepts and develop measurements. Results: As more and more micro and small business actors utilize various social media platforms (including Surya Jaya Sedadi), it becomes important to choose various existing social media platforms, of course the ones that best suit their needs. Conclusion: Digital marketing has become an important part in various business decisions, from product development, pricing, even to forms of interaction between people. Suggestion: For the future agenda we plan to validate the measurement of both concepts and test the proposed model with quantitative methods.